Implementasi Terapi Musik Klasik Untuk Mengurangi Kecemasan Pada Pasien Pre Operasi Sectio Caesarea Dengan Spinal Anestesi - Zidan, Fahmi; Sukmaningtyas, Wilis; Firdaus, Eza Kemal (Yayasan Inspirasi El Burhani, 2024)
Introduction: Performing a sectio caesarea is done to ensure the safety of both the mother and the baby, since there are risks and difficulties that might arise during a natural delivery. Nonpharmacological treatment, namely distraction strategies, may help pregnant women manage their anxiety before, during, and after surgery by focusing their attention away from the worries that arise regarding the health of both mother and child. Using distraction strategies might help alleviate anxiety, particularly during pregnancy, by diverting one's attention to something else. If you suffer from severe anxiety, one method to alleviate it is to listen to music. Objective: Music therapy is an example of a non-pharmacological treatment that this community service aims to put into place so that patients can enhance their physical and mental well-being through the use of structured auditory stimuli that include melody, rhythm, harmony, timbre, form, and style. Method: As a kind of community service, this activity makes use of listening to five or ten minutes of classical music on headphones. Result: Fifteen individuals (or 50.0% of the total) reported moderate anxiety levels before classical music therapy was implemented, whereas six participants (20.0% of the total) reported severe anxiety levels. Among the individuals, 10 (33.3%) reported moderate anxiety, 19 (63.3%) mild anxiety, and 1 (3.3%) severe anxiety after the use of rose aromatherapy. Conclusion: Based on the results obtained, it can be concluded that classical music therapy can reduce the anxiety level of patients before cesarean section surgery with spinal anesthesia.